PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN STAKEHOLDER PRESSURE PADA KUALITAS SUSTAINABILITY REPORT - Adi Natha, I Putu Gede Surya; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
A quality sustainability report is an important media because it can meet the demands of stakeholders in carrying out activities that affect the environment. This study aims to obtain empirical evidence of the effect of good corporate governance mechanisms and stakeholder pressure on the quality of sustainability reports. This research was conducted on all Indonesian companies registered as ASRRAT participants for the 2018-2021 period. The method of determining the sample using purposive sampling method. There were 21 sample companies, observed for four years so that 84 observations were obtained. The data analysis technique used is multiple linear regression. Based on the results of the analysis it was found that good corporate governance mechanisms and environmental pressures have a positive effect on the quality of sustainability reports. Stakeholder pressure, namely consumer pressure and shareholder pressure, has no effect on the quality of the sustainability report, while employee pressure has a negative effect on the quality of the sustainability report. The implications of this research provide empirical evidence of the application of stakeholder theory and legitimacy theory, in proving the quality of sustainability reports which are determined by the existence of good corporate governance mechanisms, environmental pressures and also employee pressures.